My little pony: friendship is magic, season 10, volume 2 ebook - Whitley, Jeremy (My Little Pony: Friendship is Magic (2012)., 2022)
Explore new worlds and go on new adventures with your favorite fillies in these graphic novels that continue the beloved animated series. The excitement never stops in these three tales! First, Twilight Sparkle is throwing the inaugural Festival of the Two Sisters since Celestia and Luna left—and she calls in the best party planner she knows to help: Pinkie Pie! So, of course, Pinkie reaches out to the best party planner she knows: Cheese Sandwich! Could there be... romance in the air? But wait, who turned off the sound? Then, Twilight Sparkle's mission to find friendship in all corners of Equestria has taken Rarity, Mage Meadowbrook, Maud, and Big McIntosh to the Kingdom of the Diamond Dogs! But instead of friendship, they find a feud! Can they figure out how to fix the fractured bond between six sisters? And in the final story, Fluttershy, Pinkie Pie, Trixie, Discord, and Capper visit Abyssinia, but their trip turns sour fast—they weren't supposed to end up in jail! Good thing Capper's old friends are pretty good cat burglars! Collects My Little Pony issues #94–97 and the 2021 Annual.